Systematic Literature Review: Konseling Kelompok Analisis Transaksional untuk Meningkatkan Keterampilan Komunikasi Interpersonal Mahasiswa - Syarofudin, Ahmad; Kusumadewi, Ari; Winingsih, Evi; Purwoko, Budi (Jurnal Bimbingan dan Konseling Ar-Rahman, 2024)
The main objective of this study was to assess the effectiveness of transactional analysis group counseling in improving interpersonal communication skills in college students. This research uses the Systematic Literature Review method with PRISMA (Preferred Reporting Items for Systematic Literature Review and Meta-Analysis) guidelines. The research data was obtained from research studies during the period 2014-2024. This study identified, evaluated, and synthesized 8 relevant scientific articles that had gone through a screening process using the PRISMA flowchart. Articles came from ScienceDirect, Google Scholar, Springer, Taylor & Francis Group online database. The results of this study are (1) the effectiveness of group counseling in improving students' interpersonal communication skills, (2) factors that influence the effectiveness of transactional analysis group counseling, and (3) the role of ego state in interpersonal communication. The conclusion of this study shows that group counseling transactional analysis is effective in improving students' interpersonal communication. For future research, it is recommended to add control variables to enrich findings and gain a deeper understanding of the effect of this approach. _____________________________________________________________Tujuan utama penelitian ini untuk menilai efektivitas konseling kelompok analisis transaksional untuk meningkatkan keterampilan komunikasi interpersonal mahasiswa. Penelitian ini menggunakan metode Systematic Literature Review dengan pedoman PRISMA (Preferred Reporting Items for Systematic Literature Review and Meta-Analysis). Data penelitian diperoleh dari studi penelitian selama periode 2014-2024. Penelitian ini mengidentifikasi, mengevaluasi, dan mensintesis 8 artikel ilmiah yang relevan dan telah melalui proses screening menggunakan PRISMA flowchart. Artikel berasal dari database online ScienceDirect, Google Scholar, Springer, Taylor & Francis Group. Hasil penelitian ini yaitu (1) efektivitas konseling kelompok dalam meningkatkan keterampilan komunikasi interpersonal mahasiswa, (2) faktor-faktor yang mempengaruhi efektivitas konseling kelompok analisis transaksional, (3) peran ego state dalam komunikasi interpersonal. Kesimpulan dalam penelitian ini menunjukan bahwa konseling kelompok analisis transaksional efektif digunakan untuk meningkatkan komunikasi interpersonal mahasiswa. Untuk penelitian selanjutnya, disarankan untuk menambahkan variabel kontrol guna memperkaya temuan dan memperoleh pemahaman yang lebih mendalam mengenai pengaruh pendekatan ini.